Seed Formation and Development in Cocoa (Theobroma Cacao L. ) - Haris, T. Chairun Nisa (1988)
A study on cocoa (Theobroma cacao L.) seed formation and development was undertaken at the Universiti Pertanian Malaysia, Serdang, Selangor, Malaysia. The plant materials used comprised of five dissimilar crossings of Sabah Mixed Hybrid. Freshly opened flowers were hand-pollinated and tagged to ascertain the date of pollination. The tagged flowers were then covered with plastic-net bags to protect them from insects and other hazards. Samples were taken at weekly intervals. Changes in the histology and germinability of seed, as well as size, weight and moisture content of both fruit and seed were determined. In addition, the effects of air drying on seed germinabi1ity was also studied. Progressive development of the endosperm and embryo started to occur eight weeks after pollination and it continued to do so until complete development was attained 11 weeks later (19th week). Physical development of the fruit and seed followed a three-phase sigmoidal pattern. The first phase was characterised by very slow growth rate of both the fruit and seed during the first eight weeks after pollination. This was fol lowed by a period of rapid increases in dimensions and weights until maximum values were reached 18 weeks after pollination. The final developmental phase (beyond the 18th week) was a period of minimal physical changes. Maximum seed dry weight was attained 22 weeks after pollination at which seeds are regarded as physiologically mature. Seed moisture content was high (above 90 percent) during the initial stages of development. It then declined steadily reaching a fairly stable value of about 40 percent approximately 25 weeks after pollination. Fruit moisture content on the other hand , remained relatively high (above 70 percent) throughout the developmental period.